Frekuensi “Ngemil”, Konsumsi Junk Food dan Screen Time dengan Kejadian Overweight pada Mahasiswa - M. Ikhsan Amar; Sulistyani Meita Dewi (Jurnal Ilmiah Kesehatan (JIKA), 2021)
Adolescents who experience nutritional status are more due to the behavior of eating a lot but not doing physical activity so what happens is that the energy that enters the body is not appropriate and far more than the energy used for activity and growth. The purpose of this study was to determine the relationship between Frequency of "Snacking", Consumption of Junk Food, Screen Time with Overweight Incidence in UPN Veteran Jakarta Students. The method in this research was quantitative and used a cross sectional study design. The sample in this study was 38 samples with the simple random sampling technique. The instrument in this study was to use a questionnaire. Based on the results, there were 36.8% of subjects with more nutrition. Based on the results of the chi square test, it shows that there is a relationship between junk food consumption (p = 0,014) and screen time (p = 0,030) with the incidence of overweight. Meanwhile, the frequency of "snacking" there was no relationship with the incidence of overweight (p = 0,093). The conclusion is that there is a relationship between junk food consumption and screen time with the incidence of overweight in adolescents. There is no relationship between the frequencies of "snacking" with the incidence of overweight in adolescents.